2020
DOI: 10.1134/s1029959920050057
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Friction-Stir Welding of 6061-T6 Aluminum Alloy

Abstract: In this work, two simple but effective strategies were proposed to optimize friction-stir welding of 6061-T6 aluminum alloy. The first one involved an optimization of welding variables to provide a combination of a relatively high welding temperature and the shortest possible thermal cycle during friction-stir welding. This inhibited precipitation coarsening in the heat-affected zone and resulted in considerable residual stress. Accordingly, the produced welds exhibited excellent strength characteristics under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 132 publications
0
4
0
Order By: Relevance
“…S1). Further microstructural details have been described elsewhere [57]. This material condition was denoted as base material throughout the manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…S1). Further microstructural details have been described elsewhere [57]. This material condition was denoted as base material throughout the manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…S2c) which presumably originated from solidification process. Further microstructural details have been described elsewhere [40].…”
Section: Methodsmentioning
confidence: 99%
“…Self-reacting friction stir welded joints exhibited comparable microstructural characteristics and zones to those generated using the conventional FSW method [20]. Owing to the inherently elevated temperatures associated with the FSW process, it commonly entails intricate precipitation phenomena in heat-treatable aluminum alloys [21]. It is revealed that FSW exhibits a host of advantages when compared with other fusion welding processes because of lower heat input it does not take the metal to a molten state.…”
Section: Introductionmentioning
confidence: 94%